Correlative factors for the location of tracheobronchial foreign bodies in infants and children - Xu, Ying (J Thorac Dis, 2018)
BACKGROUND: This study aims to analyze factors related to the location of tracheobronchial foreign bodies in infants and children, and provide help in the assessment of the disease, surgical risk and prognosis. METHODS: The clinical data of 1,060 pediatric patients with tracheobronchial foreign bodies diagnosed from January 2015 to December 2015 were retrospectively studied, the association of the location of the foreign bodies with age, gender, granulation formation, chest computed tomography and 3D reconstruction results, preoperative complications, operation time, and hospital stay was analyzed. RESULTS: The location of foreign bodies was not correlated with age, gender, operation time and length of hospital stay, but was correlated to granulation formation, chest computed tomography and 3D reconstruction results, and preoperative complications. CONCLUSIONS: The location of foreign bodies was correlated to granulation formation, the location of foreign bodies displayed by chest computed tomography, and preoperative complications.